A PROSPECTIVE STUDY ON MENINGOENCEPHALITIS IN BIHAR: EPIDEMIOLOGY TRENDS AND DIFFERENT TYPES. - Alam, Anwar; Z. R. Azad; Kumar, Baidyanath (Student's Journal of Health Research Africa, 2024)
Background: Acute meningitis and encephalitis (AME) pose a significant public health concern due to their association with central nervous system (CNS) infection. Understanding the seasonality, incidence rate, and causative agent of AME is essential for effective management and prevention strategies. The study examines Acute meningitis and encephalitis incidence, seasonality, causal microorganisms, and clinical manifestation patterns. Methods: In the prospective observational study, a total of 120 participants presenting with symptoms suggestive of CNS infection were enrolled. Inclusion criteria encompassed acute onset symptoms accompanied by fever, headache, vomiting, and meningeal signs or changes in mental status. Data collection included demographic, clinical, and vaccine history, along with biochemistry test results. Samples were collected for further testing, and data analysis such as mean and standard deviation was done using SPSS version 20.0. Result: The study revealed a mean age of 35 years with a balanced gender distribution. The incidence rate of AME was calculated at 15 cases per 100,000 population per year, with a peak incidence observed during the monsoon season. Viral etiologies, particularly viral encephalitis virus, accounted for 66.7% of cases, while bacterial pathogens, including Neisseria meningitidis and Haemophilus influenzae type b, comprised 33.3%. Common clinical manifestations included fever, headache, and vomiting, with elevated CRP levels and abnormal WBC counts noted in a significant proportion of cases. Tuberculous Meningitis emerged as the most common diagnosis, followed by Purulent Meningitis and other viral etiologies. Conclusion: The study provides valuable insights into the epidemiology and clinical characteristics of AME, highlighting the importance of comprehensive surveillance and diagnostic strategies. Early detection and targeted interventions are essential for mitigating the burden of AME and improving patient outcomes. Recommendations: Enhanced vaccination coverage, especially against encephalitis and bacterial pathogens, and rigorous surveillance and prompt diagnosis, are recommended to manage AME outbreaks and effectively reduce associated morbidity and mortality.